Unrecognized Myocardial Infarction is a Risk Factor for Future Stroke - Vinall, Maria (MD Conference Express, 2011)
This article discusses new data from a substudy of the REGARDS Study that suggested that unrecognized myocardial infarction and recognized myocardial infarction confer a similar risk of stroke and that the former, in particular, is a risk factor for future stroke in those with prevalent stroke.